(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the institutional framework and strategic significance of the Cha Ma Si (Tea and Horse Trade Agency) within the broader context of transcontinental commerce along the Silk Road. By examining the agency’s role in regulating the exchange of Chinese tea for Central Asian horses, the study highlights how tea and horses functioned as critical economic and military resources. The research draws on historical records from the Song, Yuan, and Ming dynasties to demonstrate how the Cha Ma Si evolved into one of the earliest state-controlled mechanisms for cross-cultural trade. It also analyzes the ways in which this system contributed to economic integration, border security, and the formation of early globalization processes in Eurasia.